Trend to symptom-based depression in sub-elite and sports athletes - Rêgo, D. C.; Andrade-Bastos, A. D.; de Melo, D. L. R.; Reis, G. C.; de Melo, H. M. S.; Souza, A. A.; de Oliveira, A. F. S. (Journal of Human Sport & Exercise, 2020)
The prevalence of people in mental distress has increased in recent decades and has influenced the quality of life of the population. This work seeks to investigate the trend to depression based on symptoms in sub-elite athletes and athletes, enabling to illustrate the mental health situation of these populations. The study included 50 athletes and 30 sports athletes, 7 were female and 43 were male athletes, and 8 were women and 22 were men among the sports athletes. The instruments were used for the characterization of the sample containing items to do the profile and the Beck Depression Inventory II (BDI-II). The Mann-Whitney U test for the Beck Depression Inventory among athletes and sub-elite athletes showed the lowest prevalence of symptoms among them (U=495.5, p=.011). When comparing by gender [F(1.75)=1.144, p=.288] and by age [F(2.75)=.160, p=.852], there was no statistical difference between groups. The difference was perceived regarding the trend according to the cutoff points of BDI-II. For gender and age, all athletes, except for males, showed a slight trend and in all cases, athletes were classified with minimal trend. Athletes have a minimal trend, being less vulnerable to depression than sports athletes. depression Collective sports athletes were less vulnerable than individual athletes and sportsmen, and the athlete status was associated and correlated with the trend toward symptom-based.